System odoratyviv davnoruskoukrayinskoho period (XI–XIII c.) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is devoted to the study of systems of word-odoratyviv Ukrainian language davnoruskoukrayinskoho period (XI–XIII c.). Study history vocabulary of the Ukrainian language is impossible without finding out the history of individual semantic groups. Analyzed the functioning olfactory vocabulary of period Kievan Rus material monuments and etymological dictionaries. Learning vocabulary is a traditional Ukrainian linguistics. Full history research is lexical structure of Ukrainian history is impossible without finding out some semantic groups. It definitely reflects the reality of man's knowledge, the initial step in this process is the perception. Vocabulary perception constantly in terms of attention to domestic linguists. The smell investigated in various aspects. Detailed consideration of olfactory vocabulary intended to help establish the history of individual words, systemic relations (synonymy, antonymy, generalization, differentiation, etc.). Changes in the semantics of tokens, the development of secondary values in the making, operation, etc., identify the composition of the vocabulary of the seventh «smell» on various stages of the history of Ukrainian written language. Works on odoratyvam have largely fragmented. Diachronic study olfactory vocabulary davnoruskoukrayinskoho particular period, is important for the formation and functioning of the thematic groups, identify patterns of historical lexicology Ukrainian language in general. It also led to the choice of theme of the article and its relevance. The actual material monuments of Kyivan Rus period, etymological dictionaries indicate the presence odoratyvnoyi vocabulary monuments XI–XIII с. (almost 400 examples). For the «Dictionary of Russian language XI–XVII centuries» tokens found about 225 – odoratyviv that functioned in XI–XIII centuries. This is an ancient thematic groups, the main roots of which inherited from Proto-Slavic period: von- (85 words), smrad- (almost 80), uh- (40 tokens), kad- (34 nominae). Odoratyvy have ownership of parts of different: noun (200), verb (100), far fewer adjectives. Identified word creative options derivatives.
Keywords: smell; odoratyvna vocabulary; derivative; root; token